تخطيط مسار روبوت متنقل باستخدام V-rep. - عطية, بسام; حليوه, هبه (Latakia University Journal -Engineering Sciences Series, 2017)
يشكل تخطيط المسار تحدياً كبيراً أمام إيجاد روبوتات متنقلة ذكية. ويعتبر إيجاد المسار المناسب الخالي من الاصطدامات، وبأقل زمن معالجة وطول مسار ممكن من القضايا البحثية الملّحة حالياً.وتعد طريقة شجرة البحث العشوائي السريعة RRTRapidly exploring random trees من أسرع الطرق التي تقوم بإيجاد مسار مناسب للروبوت كما أنها طريقة سهلة حسابياً ويمكن تطبيقها في بيئات متعددة الأبعاد. يستعرض هذا البحث خوارزمية RRT ويقدم تطبيقاً لتخطيط مسار حركة روبوت تفاضلي وفق هذه الخوارزمية في بيئتي عمل مختلفتين باستخدام محاكي الروبوتات V-rep. بيّن هذا البحث قدرة الخوارزمية على إيجاد مسار مناسب خلال زمن معالجة قصير نسبياً، كما أظهر قدرة المحاكي V-rep على نمذجة ومحاكاة ثلاثية الأبعاد لحركة الروبوت المتنقل بكفاءة وسلاسة.Robot navigation is challenging for building intelligence mobile robots. To find Proper possible path from starting point to target point, that reduces time and distance, avoiding collision with obstacles is a current potential research area. Rapidly exploring random trees (RRTs)is considered as one of the fastest methods to find solutions. Moreover, this algorithm is computationally efficient; therefore, it can be used in multidimensional environments. This paper reviews the RRT algorithm, and provides application of path planning to differential robot in two different workspaces using Virtual Robot Experimentation Platform )V-REP(simulator. This research clarifies the algorithm’s ability to find suitable path in relatively short time, and demonstrated the ability of V-rep to model and 3D simulate of mobile robot’s movement efficiently and smoothly.